Digital Marketing: A Case Study of Social Media Marketing of Indonesia Real Estate Companies - Widjaja, Herman; Santoso, Handri (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2024)
Real Estate industry, like other industries, is also heavily influenced by digital marketing especially the social media. Websites, Facebook, Instagram and YouTube become necessity in modern marketing of real estate. Indonesia’s real estate industry is a dynamic industry considering the country’s economy growth, population size and growth. Although several research has been conducted in this area, the topic focusing on Indonesia’s real estate Social Media Management System (SMMS) is still very limited. The qualitative comparative study is intended to explore and compare social media marketing strategy among top developers in Indonesia, and how they utilize the platforms to distribute marketing content and company’s other information. The data are collected from observation of the companies’ official websites and 138 accounts in YouTube, Facebook and Instagram. The study shows that each company has different strategy, depends on project locations, product / project size, project / product lifetime, target audience (prospects, affiliates, public in general, community etc), project’s ownership structure (fully owned, joint venture, franchise), sales / recurring / operational, management of social media team. Among the surveyed platforms, Instagram has been the most popular to distribute sales information for either recurring products, sales products group of products and even corporate or general public information.